RESEÑA de: FERNÁNDEZ-SORIA, J.M.; LÓPEZ, M.; CRUZ, J.I.; BASCUÑÁN, J.; MENGUAL, S.; GARCÍA, S.; LLORET, C.; y GRAU, R. (EDS.) (2016): La formación inicial del profesorado de educación secundaria (Valencia: Tirant Humanidades). ISBN: 978-84-16556-67-0 - Revesado Carballares, David (Revista Española de Educación Comparada, 2017)
——